The Relationship Of Children Who Attend Early Childhood Education (PAUD) With Motor Development - Hariyanti Haris; Siringoringo, Edison; Nirmawati (Jurnal Life Birth, 2019)
A report by United Childrenâ€™s Fund (UNICEF), (2017) Paud that of 200 million children under 5 years in developing countries, one-third of the potential children to develop are not met. Unfulfilled developments are caused by several factors, namely, poverty, malnutrition, high levels of family stress and the environment that causes children to span violence, abuse, and lack of attention and learning opportunities. The purpose of this study was to find out the relationship of children who attended early childhood education (PAUD) with motoric development in the Artika District of Bulukumba District in 2018. This research method uses an analytic design with a cross-sectional approach. The population in this study were children who attended PAUD in Tk Artika as many as 35 respondents, the sample of this study were 35 respondents with a total sampling method. The results of the analysis of the relationship of children who attended PAUD with motor development in the Artika Kindergarten of Bulukumba District in 2018, with the fisher statistic test, with the level of trust (Î± = 0.05). Based on the test result obtained values (Ï = 0.025) then H0 is rejected and Ha is accepted. This study concludes that there is a relationship between children who attend PAUD with motor development in the Artika District of Bulukumba Regency in 2018. It is suggested that the result of this study can be used as scientific reading material in the library and can also be used as reference material for a student who studies similar problems.